2008
DOI: 10.1128/iai.01134-07
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Immunosubunit Multicatalytic Endopeptidase Complex-Like 1 Is a T-Cell-Intrinsic Factor Influencing Homeostatic Expansion

Abstract: Homeostatic regulatory mechanisms maintain the constant ratios between different lymphocyte subsets in the secondary lymphoid organs. How this dynamic equilibrium is achieved, in particular following the clonal expansion and subsequent contraction of different cells after infection, remains poorly understood. Expression of the proteasome immunosubunits has been shown to influence not only major histocompatibility complex class I (MHC-I) antigen processing and thereby T-cell responses, but also the CD4/CD8 T-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 20 publications
3
48
0
Order By: Relevance
“…Peptides with the largest fold differences in abundance are listed in Table I, and the full list of peptides is available in supplemental Table S1. In accordance with our data on MIP abundance, flow cytometry analyses revealed that, as previously shown using WT versus dKO spleen lymphocytes (12), expression of cell surface H2D b and H2K b was higher by approximately 2.1-fold on WT than dKO DCs (Fig. 3B).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Peptides with the largest fold differences in abundance are listed in Table I, and the full list of peptides is available in supplemental Table S1. In accordance with our data on MIP abundance, flow cytometry analyses revealed that, as previously shown using WT versus dKO spleen lymphocytes (12), expression of cell surface H2D b and H2K b was higher by approximately 2.1-fold on WT than dKO DCs (Fig. 3B).…”
Section: Resultssupporting
confidence: 92%
“…Thus, the generation of epitopes like that one would not be blocked by pharmacological inhibitors. Our observation that IPs increase MIP abundance fits well with in vitro proteasome digestion experiments suggesting IPs have greater efflux and cleavage rates than CPs (19,20) and with the decreased cell surface levels of MHC I molecules on Lmp7 Ϫ/Ϫ and Lmp7 Ϫ/Ϫ Mecl1 Ϫ/Ϫ splenocytes (12). For reasons presented in the Introduction, it was not possible to extrapolate from previous in vitro proteasome digestion experiments the overall impact of IPs on the diversity of the MIP repertoire generated in vivo.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…additional immunological functions. Immunoproteasome deficiency or inhibition affects T cell survival, expansion, and differentiation (Basler et al, 2004;Chen et al, 2001;Kalim et al, 2012;Moebius et al, 2010;Muchamuel et al, 2009;Zaiss et al, 2008), cytokine production (Basler et al, 2011;Basler et al, 2010;Basler et al, 2014;Muchamuel et al, 2009), and progression of autoimmune conditions (Basler et al, 2015). Moreover, mutations in LMP7 and LMP2 in humans cause complex autoimmune and inflammatory phenotypes .…”
Section: Discussionmentioning
confidence: 99%
“…As monocytes replenish the pool of macrophages and dendritic cells in the body, we can assume a presence of immunoproteasome in these cells as well. T cells show a constitutive expression of all three molecules and the immunoproteasome facilitates protein homeostasis and cell proliferation in these cells (63). Because PBMCs are mainly a mixture of macrophages, monocytes, and lymphocytes we can expect that we would identify the immunoproteasome here as well.…”
Section: Discussionmentioning
confidence: 93%